Negara dan Upaya Deteksi Dini Terhadap Ideologi Radikalisme - Agus Triwaskito; Hermandar Puteh (Budapest International Research and Critics University, 2017)
This article argues that here is no other choice for this nation other than to implement a soft approach in completing the terrorism case. This approach might be able to answer the question why terrorism arose in Indonesia and how to deal with it. In addition, it requires the courage of the wider community to immediately report when finding indications or events that lead to acts of terrorism.